Impact of business ethics on employee’s productivity and organization growth: Case study at Emaar Properties Corporation, Dubai, UAE - Al Armoti, Ayman; Al Meqbali , Hamad Abdullah; Noor, Abdullah Saleh (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
Business ethics not only upgrades the corporations’ working standards but also innovates employees’ aptitude for effective project management. Due to business ethics implementation, Emaar Properties is a multinational real estate developmental corporation. In Emaar Properties, business ethics casts a beneficial impact on stakeholders’ involvement, employee loyalty, and consumers’ satisfaction with the latest product portfolio. This paper yields the business ethics practices within Emaar and the reasons for being engaged in such practices. Moreover, the paper inspects Emaar’s ethical behavior in several activities, scrutinizes if the company has ever been penalized for any unethical behavior, and provides some essential recommendations for management concerning ethical behaviors.